(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
In this scientific article the analysis of labor protection management systems in higher education institution is conducted. The main approaches to the organization of occupational safety and health, as well as their effectiveness in the context of educational institutions are considered. Particular attention is paid to the comprehensive system analysis of the actions of managers, occupational safety specialists and students in a particular area of occupational safety and training. Recommendations for improving the labor safety management system to enhance the safety of students and employees are offered.